2021
DOI: 10.1016/j.ijcard.2021.02.079
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor dysfunction in patients with angina and nonobstructive coronary artery disease is dominated by vasospasm

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…The CFT was performed in accordance with the standardized protocol and as described earlier by Konst et al ( 10 ) and Ong et al ( 15 ). In short, patients were instructed to withhold all vasoactive medication and methylxanthine-containing substances, such as coffee and bananas, for 24–48 h before the procedure, depending on half-life time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CFT was performed in accordance with the standardized protocol and as described earlier by Konst et al ( 10 ) and Ong et al ( 15 ). In short, patients were instructed to withhold all vasoactive medication and methylxanthine-containing substances, such as coffee and bananas, for 24–48 h before the procedure, depending on half-life time.…”
Section: Methodsmentioning
confidence: 99%
“…CMD (ADE+) was present when measurements showed an abnormal CFR <2.0 and/or an abnormal IMR ≥ 25, as defined by current consensus documents ( 21 ). The definitions of epicardial or microvascular spasm (ACH+) were defined in line with these guidelines as follows ( 10 , 21 , 22 ): epicardial vasospasm was defined as a focal or diffuse epicardial coronary diameter reduction ≥90% in response to ACH, compared to the relaxed state after intracoronary nitroglycerin infusion, with a reproduction of (recognizable) symptoms and ischemic ECG changes. Microvascular spasm was diagnosed when the patient experienced the reproduction of recognizable symptoms with ischemic ECG changes, in the absence of ≥90% epicardial diameter reduction during ACH infusion ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot distinguish between epicardial and microvascular vasospasm and, most essential, does not correlate well with invasively assessed vasospasm ( 15 ). This is an important limitation since vasospasm is the most prevalent endotype in patients with coronary vascular dysfunction, occurring in 81–97% of patients diagnosed with coronary vascular dysfunction, while an abnormal CFR or microvascular resistance without vasospasms occurred in only 3–19% ( 52 , 66 , 67 ). Therefore, one should realize that the diagnosis of coronary vascular dysfunction is easily missed with non-invasive diagnostics.…”
Section: Demonstration Of Coronary Vascular Dysfunctionmentioning
confidence: 99%
“…Another study in 391 patients with angina and no obstructive CAD utilized both adenosine and acetylcholine and found 52% had isolated CMD (low CFR), 17% had isolated vasospasm, and 21% had a mixed endotype (102). In contrast, a recent study in 111 ANOCA patients found 63% had isolated vasospasm, only 3% had isolated impaired vasodilation, and 34% had a mixed endotype (105). In sum, a considerable subset of ANOCA patients should be expected to suffer from isolated vasospasm which will inherently go undetected by TTDE CFVR evaluation.…”
Section: Other Modalitiesmentioning
confidence: 99%